Rethinking global health training: making the links between theory and practice - Fisher, Lucas AB; Aristizabal Londono, Candelaria; Cropper, Kayla; Beresh, Graham; Alhassan, Jacob AK (Canadian Medical Education Journal, 2025)
Implication Statement International medical electives are viewed as an opportunity for medical students to experience global health firsthand and improve cultural humility. Despite its potential benefits, concerns have been raised regarding harms during placements. These need to be addressed to ensure that international electives are conducted ethically and not only benefit learners but also the communities involved. The University of Saskatchewan has transformed its global health certificate, Making the links, in an effort to address existing concerns. We seek to share the program’s approach and its value to us. Other centres may introduce this approach to help train more equity-oriented healthcare workers.